THE ROLE OF E-FILING IN IMPROVING TAXPAYER COMPLIANCE IN INDONESIA - Aliah, Nur (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2020)
The advancement of technology has made people prefer a practical and easy. E-filing is one of the technological advances used by the Indonesian Directorate General of Taxes. The use of an online tax application is also carried out in order to improve Indonesia's ranking in the list of Ease of Doing Business (EODB) in the world with one of the indicators is the use of technology to shorten the bureaucracy and improve time and cost efficiency . The purpose of writing this scientific journal is to determine the role of using e-filing applications for taxpayer compliance in Indonesia. The research method used in this research is to use a qualitative descriptive method. The type of data in this study is qualitative data, where data is presented in the form of words that contain meaning in the form of data that is processed through interviews and explanations about e-filing. Data collection was carried out using interview methods and other source. The results of research conducted indicate that the use of e-filing is able to increase taxpayer compliance every year. In this case the government is expected to continue to develop the e-filing application and conduct socialization to various groups of people so that taxpayers become more about funding the use of e-filing applications in SPT reporting so that the taxpayer compliance targets are realized according to the target every year.